NMR analysis of a series of substituted pyrazolo[3,4-d]pyrimidines-4-amines - Rodrigues, Lígia M. (2009)
A series of twenty one substituted pyrazolo[3,4-d]pyrimidines-4-amines were studied by 1H and 13C NMR. The application of two-dimensional techniques, HMQC and HMBC, allowed the complete assignment of the spectra for all the compounds.